IN RAISING CHILDREN OF PRESCHOOL AGE GETTING AWAY OF AGGRESSION - Maftuna Abdimuminova Alisher qizi (Galaxy International Interdisciplinary Research Journal, 2021)
The article provides recommendations on the prevention and elimination of the causes of aggression with the help of biological and psychological knowledge in the upbringing of aggressive children in preschool education.